2008
DOI: 10.1007/s10350-008-9227-2
|View full text |Cite
|
Sign up to set email alerts
|

Significant Rectal Bleeding as a Complication of a Fecal Collecting Device: Report of a Case

Abstract: We report the case of 65-year-old man who developed massive rectal bleeding associated with the use of a fecal collecting device: the Flexi-Seal Fecal Management System. A colonoscopy showed an acute laceration of the anterior rectal wall mucosa, 6 cm from the anal verge, with active bleeding. The tear was most likely the result of an acute event, such as sudden movement of the device within the rectum or trauma sustained during insertion. Massive transfusion was required, and surgical endoscopic treatment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…(11)(12)(13) Fortunately, in the present study, we did not encounter such problems with the use of the Flexi-Seal ® FMS. However, it may be premature, based on the findings of the present study, to conclude that the use of the Flexi-Seal ® FMS is without any danger.…”
Section: Discussionmentioning
confidence: 58%
“…(11)(12)(13) Fortunately, in the present study, we did not encounter such problems with the use of the Flexi-Seal ® FMS. However, it may be premature, based on the findings of the present study, to conclude that the use of the Flexi-Seal ® FMS is without any danger.…”
Section: Discussionmentioning
confidence: 58%
“…Relative contraindications for the use of this device may be rectal perforations or rectal ulcers. Tenesmus and rectal bleeding have been described as occasional complications [15].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies (n=7)11 1520 were prospective cohort studies, with one case study12 and one case series21 study identified. One study did not describe their research methodology 13…”
Section: Methodsmentioning
confidence: 99%
“…FI is one of the associated problems with prolonged immobilisation, especially among the elderly and critically ill. Nursing care of bedridden patients with FI is more labour intensive and increases the risk of perianal wound infection 12. Indeed, FI related problems have the potential to influence length of stay in hospital, gaining hospital infections and increasing the amount of nursing interventions required 13…”
Section: Introductionmentioning
confidence: 99%